1998
DOI: 10.1021/bi971455c
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopiazonic Acid Effect on Ca2+-Dependent Conformational States of the Sarcoplasmic Reticulum ATPase. Implication for the Enzyme Turnover

Abstract: The affinity of sarcoplasmic reticulum Ca2+-ATPase for cyclopiazonic acid is dependent on the conformational state of the enzyme. It is high in the absence of Ca2+ but low in its presence. When Ca2+ was added to the enzyme in the presence of equimolar toxin, the apparent rate constant for Ca2+ binding was 0.6 min-1 when measured at 37 degrees C. The apparent equilibrium constant for Ca2+ dissociation increased from 0.2 to 0.6 microM at neutral pH, and from 5.9 to 37 microM at pH 6.0. The apparent equilibrium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
(65 reference statements)
4
28
0
Order By: Relevance
“…With an ATP concentration of 1 mM, SERCA is completely inhibited at a CPA/SERCA molar ratio of approximately 10 (Soler et al, 1998). Furthermore, enzyme activity is observed to recover at a CPA/ SERCA molar ratio of 1 when the Ca 2ϩ concentration is raised, which is consistent with the competitive character of CPA and Ca 2ϩ (Soler et al, 1998). These results suggest that ATP and Ca 2ϩ can protect against CPA inhibition.…”
Section: Use In Smooth Musclesupporting
confidence: 66%
See 1 more Smart Citation
“…With an ATP concentration of 1 mM, SERCA is completely inhibited at a CPA/SERCA molar ratio of approximately 10 (Soler et al, 1998). Furthermore, enzyme activity is observed to recover at a CPA/ SERCA molar ratio of 1 when the Ca 2ϩ concentration is raised, which is consistent with the competitive character of CPA and Ca 2ϩ (Soler et al, 1998). These results suggest that ATP and Ca 2ϩ can protect against CPA inhibition.…”
Section: Use In Smooth Musclesupporting
confidence: 66%
“…Nonetheless, CPA effect on the enzyme is likely not restricted to the ATP-binding process since it causes additional inhibition of the ATPase at concentrations above the stoichiometric levels (Plenge-Tellechea et al, 1997). With an ATP concentration of 1 mM, SERCA is completely inhibited at a CPA/SERCA molar ratio of approximately 10 (Soler et al, 1998). Furthermore, enzyme activity is observed to recover at a CPA/ SERCA molar ratio of 1 when the Ca 2ϩ concentration is raised, which is consistent with the competitive character of CPA and Ca 2ϩ (Soler et al, 1998).…”
Section: Use In Smooth Musclementioning
confidence: 99%
“…8B). The uncoupled state of the enzyme was protected from CPA, an E 2 -directed inhibitor of the enzyme (33). Such inhibition by CPA was patent when the lumenal Ca 2ϩ load was relieved by the addition of Ca 2ϩ ionophore (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The E 1 -E 2 cycle (coupled route) involves dissociation of lumenal Ca 2ϩ from E 1 P⅐Ca 2 and further release of P i from E 2 P. The E 1 cycle (uncoupled route) consists of the release of P i from E 1 P⅐Ca 2 before Ca 2ϩ dissociation to the cytoplasmic medium and the absence of E 2 and E 2 P species. The mechanism of intramolecular uncoupling was confirmed by using the high affinity inhibitor CPA (31)(32)(33) and measuring UTP hydrolysis under the conditions described in Fig. 8.…”
Section: Camentioning
confidence: 94%
“…Intriguingly, early kinetic analyses on SERCA (29) showed that the inhibitor cyclopiazonic acid (CPA) modifies SERCA in a way very similar to the CPZ modification of NKA. Transport studies have also shown that CPA uncouples SERCA and reduces the transport stoichiometry to one-half (30).…”
Section: Discussionmentioning
confidence: 99%